2004
DOI: 10.1121/1.1781329
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of temporal information in various frequency regions for consonant identification in quiet and in noise

Abstract: The relative importance of temporal information in broad spectral regions for consonant identification was assessed in normal-hearing listeners. For the purpose of forcing listeners to use primarily temporal-envelope cues, speech sounds were spectrally degraded using four-noise-band vocoder processing. Frequency-weighting functions were determined using two methods. The first method consisted of measuring the intelligibility of speech with a hole in the spectrum either in quiet or in noise. The second method c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
67
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 29 publications
8
67
2
Order By: Relevance
“…The draw has been due to sparse but increasingly conclusive evidence that high-frequency energy (HFE, defined here as the energy in the 8-and 16-kHz octave bands or 5.7-22 kHz) plays a larger perceptual role in speech perception than previously assumed. The percepts impacted by HFE that have been reported thus far are speech and voice quality (Olson, 1947;Moore and Tan, 2003;Moore et al, 2010;Monson et al, 2011), speech source localization (Best et al, 2005), speech intelligibility (Lippmann, 1996;Stelmachowicz et al, 2001;Apoux and Bacon, 2004;Moore et al, 2010), and child word-learning (Stelmachowicz et al, 2007;Pittman, 2008). Some studies indicate that HFE could also play a role in the perception of voice disorders (de Krom, 1995;Hartl et al, 2003) and in talker identification (Hayakawa and Itakura, 1995;White, 2001;Liss et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The draw has been due to sparse but increasingly conclusive evidence that high-frequency energy (HFE, defined here as the energy in the 8-and 16-kHz octave bands or 5.7-22 kHz) plays a larger perceptual role in speech perception than previously assumed. The percepts impacted by HFE that have been reported thus far are speech and voice quality (Olson, 1947;Moore and Tan, 2003;Moore et al, 2010;Monson et al, 2011), speech source localization (Best et al, 2005), speech intelligibility (Lippmann, 1996;Stelmachowicz et al, 2001;Apoux and Bacon, 2004;Moore et al, 2010), and child word-learning (Stelmachowicz et al, 2007;Pittman, 2008). Some studies indicate that HFE could also play a role in the perception of voice disorders (de Krom, 1995;Hartl et al, 2003) and in talker identification (Hayakawa and Itakura, 1995;White, 2001;Liss et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This highfrequency energy (HFE) in singing and speech has traditionally been neglected in scientific research, but recent findings show that HFE in speech and singing is of perceptual significance and therefore merits some attention. Among the percepts affected by HFE are voice and speech quality F€ ullgrabe et al, 2010;Moore and Tan, 2003), speech intelligibility (Badri et al, 2011;Moore et al, 2010;Pittman, 2008;Apoux and Bacon, 2004;Lippmann, 1996), and localization of speech (Best et al, 2005). Furthermore, humans are apparently sensitive to subtle changes in HFE level in singing .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] A few studies that have examined speech and voice quality have suggested that HFE plays a role in the perceived quality of voice. As early as 1957, Olson 17 reported that listeners preferred live full bandwidth speech (and music) to that acoustically low-pass filtered at 5 kHz.…”
Section: Introductionmentioning
confidence: 99%